2011
DOI: 10.1038/nmat3176
|View full text |Cite
|
Sign up to set email alerts
|

H-atom relay reactions in real space

Abstract: Hydrogen bonds are the path through which protons and hydrogen atoms can be transferred between molecules. The relay mechanism, in which H-atom transfer occurs in a sequential fashion along hydrogen bonds, plays an essential role in many functional compounds. Here we use the scanning tunnelling microscope to construct and operate a test-bed for real-space observation of H-atom relay reactions at a single-molecule level. We demonstrate that the transfer of H-atoms along hydrogen-bonded chains assembled on a Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 46 publications
1
93
1
Order By: Relevance
“…It is also noteworthy that the chiral inversion is not a simple rotation or displacement of the whole Pb 3 configuration but rather a complex motion involving two Pb and three Si atoms, where Pb-Si exchanges and Pb-and Si displacements are indeed promoted in concert. This feature is strikingly different from any reported switches involving only single-atom/molecule processes [10][11][12][13][14][15][16][17][18][19][20] , thus being a new type of switch.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…It is also noteworthy that the chiral inversion is not a simple rotation or displacement of the whole Pb 3 configuration but rather a complex motion involving two Pb and three Si atoms, where Pb-Si exchanges and Pb-and Si displacements are indeed promoted in concert. This feature is strikingly different from any reported switches involving only single-atom/molecule processes [10][11][12][13][14][15][16][17][18][19][20] , thus being a new type of switch.…”
Section: Resultscontrasting
confidence: 84%
“…Since this pioneering work, extensive studies using STM/AFM have demonstrated a variety of atomic-scale switches composed of not only an adsorbed atom but also adsorbed molecules and native surface atoms. In all cases, reversible switches could be operated in a controlled way through their single-atom/molecule processes such as lateral/vertical displacements [11][12][13][14] , rotational motions [15][16][17] and conformational changes [18][19][20] . Nevertheless, most switches devised thus far need to be operated at cryogenic temperatures, while controllability at roomtemperature (RT) environment is essential for the many practical applications that await this new technology.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This breakthrough in fundamental science and in nanotechnology has stirred a lot of attention as it became possible to manipulate adsorbates and to induce reactions on the atomic scale. On the one hand, these tunneling experiments provide perfect toy systems to learn chemical rules; 16,17 on the other hand, promising bottom-up techniques for creating nanometer-scaled devices become feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning probe microscope studies focus increasingly on measuring fast time-dependent processes at atomic dimensions, such as spin [1][2][3][4] and charge 5,6 dynamics or molecular motion. [7][8][9][10] Heterodyne frequency mixing 11 and pump-probe excitation schemes 2,[12][13][14][15] have been put forward as techniques to measure repetitive variations of the tunnel current in a scanning tunneling microscope (STM). Such techniques overcome practical limitations caused by the small bandwidth of high-gain current amplifiers and circumvent shot noise problems that arise in fast measurements of small electric currents.…”
mentioning
confidence: 99%